Integrasi Nilai-Nilai Islam dalam Sistem Pendidikan Modern di Era Globalisasi - Tyeva Agil Nadiansyah; Alif Akmal Al Irsyad; Herlini Puspika Sari (Moral : Jurnal kajian Pendidikan Islam, 2026)
The rapid development of globalization has significantly influenced modern education systems, requiring not only the advancement of knowledge but also the strengthening of moral and spiritual values. This study aims to analyze the integration of Islamic values within modern education systems in the era of globalization. The research employs a qualitative approach with a library research method, utilizing various academic sources such as books, journals, and relevant documents. Data are collected through documentation techniques and analyzed using content analysis to interpret and synthesize existing theories and findings. The results indicate that the integration of Islamic values can be effectively implemented through curriculum development, teaching methods, digital technology utilization, and the role of educators as value transmitters. Furthermore, the study reveals that a holistic and systematic integration approach is essential to balance intellectual, emotional, and spiritual development in learners. The implications of this research highlight the importance of developing an integrative education model that aligns Islamic principles with modern scientific and technological advancements, in order to produce individuals who are not only academically competent but also possess strong moral character in facing global challenges.